Efficacy of Jatropha (Jatropha curcas L.) Sap Cream on Total Differential Leucocytes in Inflammatory Phase of Wound Healing on Mice Skin (Mus musculus) : A Review - Aufira Fildza Bahittah; M. Nur Salim; Triva Murtina Lubis; T. Zahrial Helmi; Abdul Harris; Wahyu Eka Sari (Jurnal Medika Veterinaria, 2023)
A wound is a damage to the integrity of the epithelium of the skin. There are three phases of wound healing process, the first phase is inflammatory phase, the second phase is fibroplasia phase, and the third is maturation phase. Inflammation that occurs during the wound healing process should be limited because it would cause the wound to undergo an abnormal healing process and pathological inflammation if it persists. The aim of this study was to determine the efficacy of jatropha (Jatropha curcas L.) sap cream on total differential leucocytes in inflammatory phase of wound healing on mice skin. The method used was literature study using qualitatSive methods. Data used in this study refers to the result of studies which have been conducted and published in national and international online journal. Result of data analysis showed that Jatropha sap cream was effectively limiting and  inhibiting the leucocytes accumulation in inflammatory area and stimulated new blood vessels formation (angiogenesis) in inflammatory phase of wound healing in mice skin. Based on the result of this study, it can be concluded that the Jatropha sap cream could reduce the number of differential leucocytes in inflammatory phase of wound healing on mice skin.